Effects of beetroot juice ingestion on physical performance in highly competitive tennis players - Lopez-Samanes, A.; Perez-Lopez, A.; Moreno-Perez, V.; Nakamura, F. Y.; Acebes-Sanchez, J.; Quintana-Milla , I.; Sanchez-Oliver, A. J.; Moreno-Perez, D.; Fernandez-Elias, V. E.; Dominguez, R. (Nutrients, 2020)
Beetroot juice (BJ) contains high levels of inorganic nitrate (NO3..) and its intake has good evidence in increasing blood nitrate/nitrite concentrations. The ingestion of BJ has been associated with improvements in physical performance of endurance sports, however the literature in intermittent sports is scarce. The aim of this study was to investigate whether BJ could improve physical performance in tennis players. Thirteen well-trained tennis players (25.4 5.1 years) participated in the study during their preparatory period for the tennis season. Subjects were randomly divided into two groups and performed a neuromuscular test battery after either BJ or placebo (PLA) consumption. Both trials were executed on two separate days, in randomized order, with one week of wash out period. The test battery consisted of serve velocity test (SVT), countermovement jump (CMJ), isometric handgrip strength (IHS), 5-0-5 agility test (5-0-5), and 10 m sprint (10-m). No significant di erences were found in SVT (1.19%; p = 0.536), CMJ (0.96%; p = 0.327), IHS (4.06%; p = 0.069), 5-0-5 dominant and nondominant side (1.11-2.02%; p = 0.071-0.191) and 10-m (1.05%; p = 0.277) when comparing BJ and PLA ingestion. Thus, our data suggest that low doses of BJ (70 mL) consumption do not enhance tennis physical performance.